Cross-Sector Partnerships as Capitalism's New Development Agents: Reconceiving Impact as Empowerment. Issue 7 (September 2020) - Vestergaard, Anne; Murphy, Luisa; Morsing, Mette; Langevang, Thilde
Cross-sector partnerships are currently praised as capitalism's key governance instrument to address development challenges. Although some concern has been raised about the effectiveness of such partnerships, little is known about their actual impact. Often it is assumed that partnership outputs transform straightforwardly into societal impact such as poverty alleviation. This article problematizes this assumption. Employing a critical micro-level study, which draws on a qualitative case study of a nongovernmental organization (NGO)–business partnership in Ghana, we examine how outputs provided by a partnership are put to use and perceived as beneficial from the point of view of its beneficiaries. The findings show that the partnership results in what we term "competences without agency" since it provides new resources and knowledge to the beneficiaries but fails to generate the conditions for these to be transformed into significant changes in their lives. Drawing on the concept of empowerment, we propose a new framework, which conceptualizes "impact as empowerment" and highlights currently unrecognized dynamics, which contribute to shaping the ability of a partnership to serve as a development agent.